Job Satisfaction and Employee Performance Shoes Industry in Tangerang Regency Banten Province - Usman, Juanda; Sukmayuda, Dede Nuary; Kurniawati, Sri (International Review of Management and Marketing, 2019)
The background of this research is how to improve employee performance shoes industry in Tangerang Regency, Banten Province. The purpose of this study is to identify and analyze influence both partial and simultaneously leadership, work compensation, work environment and job satisfaction toward employee performance Shoes Industry in Tangerang Regency, Banten Province.The research method used descriptive, verificative, causality to test the hypothesis. This study was conducted through a survey of 200 respondents from a population of 413 permanent employee in three shoes factories in Tangerang Regency, Banten Province. Instrument tests were also conducted on 30 respondents prior to field research. The research analysis used descriptive and explanatory statistic method. Data were analyzed with Structural Equation Model (SEM) using LISREL 8.7 software. The results of this study, processed by using 2nd CFA (Second Order Confirmatory Factor Analysis). This research proves that there are positive and significant influence of leadership, work compensation and work environment to job satisfaction either partially or simultaneously with coefficient of determination (R2) equal to 60%. Furthermore, this study proves that the variables of leadership, work compensation, work environment and job satisfaction influence employee performance with contribution of 85% with the most dominant variable influencing job satisfaction is work compensation. While the most dominant variables influencing employee performance is work environment. The findings of this study explain that job satisfaction variables mediate the three variables of leadership, work compensation and work environment on employee performance, so that job satisfaction variable as mediating variable, but the dominant variable influencing employee performance is work environment, especially physical environment dimension with work facility as indicator. Meanwhile, to increase job satisfaction need to pay attention to work compensation, especially in financial compensation, especially insurance. Keywords: Leadership, Work Compensation, Work Environment, Job Satisfaction, Employee Performance JEL Classifications: M12, M54, N75 https://doi.org/10.32479/irmm.7447